2014
DOI: 10.1093/mnras/stu825
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Lyα haloes around galaxies at z = 2.2–6.6: implications for galaxy formation and cosmic reionization

Abstract: We present diffuse Lyα halos (LAHs) identified in the composite Subaru narrowband images of 100 − 3600 Lyα emitters (LAEs) at z = 2.2, 3.1, 3.7, 5.7, and 6.6. First, we carefully examine potential artifacts mimicking LAHs that include a large-scale point-spread function (PSF) made by instrumental and atmospheric effects. Based on our critical test with composite images of non-LAE samples whose narrowbandmagnitude and source-size distributions are the same as our LAE samples, we confirm that no artifacts can pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
221
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(250 citation statements)
references
References 64 publications
24
221
2
Order By: Relevance
“…Note that many Lyα galaxies have a very extended Lyα halo (e.g. Ostlin et al 2009;Hayes et al 2013;Momose et al 2014). For these Green Pea galaxies, their Lyα to UV size ratios are about 2−4 (Yang et al 2017).…”
Section: And Leitherer 2013) According To the Model Calculations Inmentioning
confidence: 99%
“…Note that many Lyα galaxies have a very extended Lyα halo (e.g. Ostlin et al 2009;Hayes et al 2013;Momose et al 2014). For these Green Pea galaxies, their Lyα to UV size ratios are about 2−4 (Yang et al 2017).…”
Section: And Leitherer 2013) According To the Model Calculations Inmentioning
confidence: 99%
“…By stacking hundreds of z 2.2, z 3.1, z 3.7, and z 5.7 LAEs from deep ground-based imaging, Momose et al (2014) discovered extended Lyα emission, with scale lengths in the range of 5−10 kpc. However, by stacking their sample of LAEs Feldmeier et al (2013) just found a marginal detection at z ∼ 3.1 and a non-detection at z 2.07.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, at such small distances, the profile of the central galaxy is significantly driven by the point-spread function of the instrument (Momose et al 2014). Owing to these uncertainties,here we ignore the central galaxy and limit our calculations to distances >10 pkpc.…”
Section: Formalismmentioning
confidence: 99%
“…Nowadays, this faint emission is being proved to be nearly ubiquitousin galaxies at high redshift,   z 3 5, by means of stacking analyses Matsuda et al 2012;Feldmeier et al 2013;Momose et al 2014Momose et al , 2016anddue to the sensitivity and spatial resolution improvement of instruments such as MUSE (Bacon et al 2014). A clear understanding ofthe origin of these extended Lyα halos (LAHs; hereafter) is relevant because it yields information about the physical conditions of the circumgalactic medium (CGM) and, in turn, on the processes governing the formation and evolution of galaxies (Bahcall & Spitzer 1969).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation